REGISTER IN UKRAINIAN NEWS ANCHOR PUBLISHED BY TIMES RADIO: : IMPACT ON AUDIENCE ENGAGEMENT AND UNDERSTANDING - Priandini, Nadia Desy (Language Horizon: Journal of Language Studies, 2025)
This research investigates the impact of register, as utilized by Ukrainian news anchors in broadcasts presented by Times Radio, on audience engagement and comprehension. Register refers to the variation of language use shaped by social context, encompassing tone, style, and lexical choices. The study applies Biber’s Multi-Dimensional Analysis of Register (1988) as the theoretical framework to identify linguistic features and stylistic dimensions that distinguish formal, technical, colloquial, and conversational news delivery. Using qualitative methods and documentation techniques, this research analyzes a corpus of Ukrainian news broadcasts to examine how different registers influence audience perception and understanding. The analysis focuses on how linguistic choices—such as informational density, narrative involvement, and referential specificity—affect audience engagement. Furthermore, it explores whether specific registers are more effective for enhancing comprehension and whether register choices vary across topics or individual anchors. By applying Biber’s approach, the study seeks to clarify how registers function in Ukrainian news media and how they shape the audience’s cognitive and emotional reception. The findings are expected to contribute to a deeper understanding of how linguistic registers influence news consumption, providing valuable insights for media organizations seeking to optimize communication strategies and improve audience engagement in a multilingual and dynamic media environment.